2020
DOI: 10.1101/2020.03.28.20040097
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In-flight Transmission Cluster of COVID-19: A Retrospective Case Series

Abstract: Objectives: No data were available about in-flight transmission of SARS-CoV-2. Here, we report an in-flight transmission cluster of COVID-19 and describe the clinical characteristics of these patients.Methods: After a flight, laboratory-confirmed COVID-19 was reported in 12 patients. Ten patients were admitted to the designated hospital. Data were collected from 25 th January to 28 th February 2020. Clinical information was retrospectively collected.Results: All patients are passengers without flight attendant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
(39 reference statements)
3
19
0
Order By: Relevance
“…In nine studies that reported on close contacts of infected individuals and aggregated data from clusters of both asymptomatic and symptomatic people with SARS-CoV-2 the summary estimate was 14% (95% CI 8%-23%, prediction interval 2%-53%) [36,47,60,62,66,72,105,108,111]. We included 12 studies (n = 675 people) that reported on outbreak investigations arising from a single symptomatic person or from the country's first imported cases of people with COVID-19 [32,43,48,58,61,68,71,90,94,95,97,100]. Four of the outbreaks involved nursing homes [58,68,71,94] and four involved occupational settings [43,61,90,95].…”
Section: Proportion Of People With Asymptomatic Sars-cov-2 Infectionmentioning
confidence: 99%
“…In nine studies that reported on close contacts of infected individuals and aggregated data from clusters of both asymptomatic and symptomatic people with SARS-CoV-2 the summary estimate was 14% (95% CI 8%-23%, prediction interval 2%-53%) [36,47,60,62,66,72,105,108,111]. We included 12 studies (n = 675 people) that reported on outbreak investigations arising from a single symptomatic person or from the country's first imported cases of people with COVID-19 [32,43,48,58,61,68,71,90,94,95,97,100]. Four of the outbreaks involved nursing homes [58,68,71,94] and four involved occupational settings [43,61,90,95].…”
Section: Proportion Of People With Asymptomatic Sars-cov-2 Infectionmentioning
confidence: 99%
“…27 Other indoor case clusters have been reported within fitness gyms, boxing matches, call centres, and churches, where people might sing, pant, or talk loudly. 28 -30 Interestingly, there have been few reports of outbreaks on aeroplanes, 31 which may reflect current low volume of passengers, lack of contact tracing, or relatively low risk because speaking is limited. Although publication bias is likely (events linked to outbreaks are more likely to be reported than events where no outbreak occurred), well documented stories of outbreaks demand a scientific explanation.…”
Section: Force Of Emission Ventilation Exposure Timementioning
confidence: 99%
“…Using the same approach has proven effective in controlling virus transmission in China over the last 6 weeks in combating the COVID-19 outbreak [21]. It has been reported that it may be possible for COVID-19 to be transmitted during flights, which has prompted the mandatory wearing of N95 facemasks for crew and passengers on any incoming flights to China, and when known positive COVID-19 cases are onboard, isolation in a screened-off section of the aircraft and the wearing of fully protective gowns, face masks and goggles [26]. Thus, during the repatriation flight and during the short interval in China prior to swab testing, stringent quarantine precautions were used, making infection during the repatriation flight and upon return to China unlikely.…”
Section: Discussionmentioning
confidence: 99%